PANDEMI COVID-19: KINERJA KEUANGAN PERUSAHAAN HEALTHCARE YANG TERDAFTAR DI BEI - Annisa Devi Barnaditya Putri; Eko Prasetio, Januar (Jurnal Analisa Akuntansi dan Perpajakan, 2024)
The research aims to analyze differences in the financial performance of companies in the healthcare sector listed on the Indonesia Stock Exchange (IDX) between 2019-2022. This study compares financial performance before and when, before and after, during and after as well as before, when and after the Covid-19 pandemic. Financial performance is measured using cash ratio variables, smooth ratio, debt billing periods, fixed asset turnover, remuneration on fixed property, equity return and stock turnover. Normality test method using Shapiro-wolf test and hypothesis analysis technique using non-parametric wilcoxon signed rank test. Based on research, there are differences between financial performance before and during the pandemic, as well as before and after it. Current and post-covid financial performance as well as before, during and after the Covid-19 pandemic there are no differences.